Frontiers in Statistical Quality Control 6 2001
DOI: 10.1007/978-3-642-57590-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance Sampling by Variables under Measurement Uncertainty

Abstract: Abstract. The paper discusses the influence from measurement uncertainty in case of acceptance sampling by variables. Two kinds of measurement uncertainty are considered in this paper, one is the pure random noise changing from one item to the other. The other type of measurement error considered is a constant error on all items in a lot, but where the error varies from lot to lot. The largest deterioration on the operating characteristics is seen from the low frequency measurement error type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…When apparent measurements are imprecise, the condition ¤ 1 holds. Assuming that Y and Z are normally distributed, Mei et al (1975), Owen and Chou (1983), Basnet and Case (1992), Fang and Zhang (1995), Wilrich (2000), and Melgaard and Thyregod (2001) studied the single sampling variables plans. Mei et al (1975), Owen and Chou (1983), and Wilrich (2000) suggested an increase in sample size to mitigate the effect of inaccuracy in measurements.…”
Section: Measurement Error Correction For Variables Inspectionmentioning
confidence: 99%
“…When apparent measurements are imprecise, the condition ¤ 1 holds. Assuming that Y and Z are normally distributed, Mei et al (1975), Owen and Chou (1983), Basnet and Case (1992), Fang and Zhang (1995), Wilrich (2000), and Melgaard and Thyregod (2001) studied the single sampling variables plans. Mei et al (1975), Owen and Chou (1983), and Wilrich (2000) suggested an increase in sample size to mitigate the effect of inaccuracy in measurements.…”
Section: Measurement Error Correction For Variables Inspectionmentioning
confidence: 99%
“…In the last edition of the standard ISO 3951-2 [8] an informative annex has been introduced for the purpose of taking into accout a non-negligible random measurement error. The case of a non-negligible residual systematic measurement error is analysed in [11] (a reference which appears among those listed in the bibliography of [8]). It is worth comparing the frequentist result in [11] with the Bayesian one obtained here and reported in table 1, both valid for zero mean, normal systematic measurement error.…”
Section: Frequentist Approachmentioning
confidence: 99%
“…The case of a non-negligible residual systematic measurement error is analysed in [11] (a reference which appears among those listed in the bibliography of [8]). It is worth comparing the frequentist result in [11] with the Bayesian one obtained here and reported in table 1, both valid for zero mean, normal systematic measurement error. From section 3 of [11] we have 24) is substituted in (33) when assuming normal or rectangular residual systematic error, respectively.…”
Section: Frequentist Approachmentioning
confidence: 99%
“…Measurement errors in the design of single sampling variables plans is considered by the authors in , and . The apparent measurements ( X ′ ) subject to errors are assumed to follow N ( ϵ , τ ) instead of the standardized N (0,1) distribution for the true measurements X .…”
Section: Risk Analysismentioning
confidence: 99%
“…The impact of measurement and model uncertainties on the combined attributes-variables plan is discussed next. Measurement errors in the design of single sampling variables plans is considered by the authors in [32][33][34][35][36][37], and [38]. The apparent measurements (X ′ ) subject to errors are assumed to follow N( , ) instead of the standardized N(0, 1) distribution for the true measurements X.…”
Section: Risk Analysismentioning
confidence: 99%